Modulation of the Wnt pathway through inhibition of CLK2 and DYRK1A by lorecivivint as a novel, potentially disease-modifying approach for knee osteoarthritis treatment. Issue 9 (September 2019) - Deshmukh, V.; O'Green, A.L.; Bossard, C.; Seo, T.; Lamangan, L.; Ibanez, M.; Ghias, A.; Lai, C.; Do, L.; Cho, S.; Cahiwat, J.; Chiu, K.; et al.
Summary: Objectives: Wnt pathway upregulation contributes to knee osteoarthritis (OA) through osteoblast differentiation, increased catabolic enzymes, and inflammation. The small-molecule Wnt pathway inhibitor, lorecivivint (SM04690), which previously demonstrated chondrogenesis and cartilage protection in an animal OA model, was evaluated to elucidate its mechanism of action. Design: Biochemical assays measured kinase activity. Western blots measured protein phosphorylation in human mesenchymal stem cells (hMSCs), chondrocytes, and synovial fibroblasts. siRNA knockdown effects in hMSCs and BEAS-2B cells on Wnt pathway, chondrogenic genes, and LPS-induced inflammatory cytokines was measured by qPCR. In vivo anti-inflammation, pain, and function were evaluated following single intra-articular (IA) lorecivivint or vehicle injection in the monosodium iodoacetate (MIA)-induced rat OA model. Results: Lorecivivint inhibited intranuclear kinases CDC-like kinase 2 (CLK2) and dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A). Lorecivivint inhibited CLK2-mediated phosphorylation of serine/arginine-rich (SR) splicing factors and DYRK1A-mediated phosphorylation of SIRT1 and FOXO1. siRNA knockdowns identified a role for CLK2 and DYRK1A in Wnt pathway modulation without affecting β-catenin with CLK2 inhibition inducing early chondrogenesis and DYRK1A inhibition enhancing mature chondrocyte function. NF-κB and STAT3 inhibition by lorecivivint reduced inflammation. DYRK1A knockdown was sufficient for anti-inflammatory effects, while combined DYRK1A/CLK2 knockdown enhanced this effect. In the MIA model, lorecivivint inhibited production of inflammatory cytokines and cartilage degradative enzymes, resulting in increased joint cartilage, decreased pain, and improved weight-bearing function. Conclusions: Lorecivivint inhibition of CLK2 and DYRK1A suggested a novel mechanism for Wnt pathway inhibition, enhancing chondrogenesis, chondrocyte function, and anti-inflammation. Lorecivivint shows potential to modify structure and improve symptoms of knee OA.